2001
DOI: 10.1034/j.1399-3054.2001.1120107.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of senescing cotyledons of clusterbean to water stress in moderate and low light: Possible photoprotective role ofβ‐carotene

Abstract: Senescence of clusterbean (Cyamopsis tetragonoloba L.) cotyledons in moderate light (12 W m-2) brings about a loss in the pigments, enhanced lipid peroxidation and a decline in PS II photochemical activity without any loss either in Dl protein or in the level of beta-carotene. The senescence syndrome is aggravated in the cotyledons of water-stressed seedlings with an increase in thylakoid lipid peroxidation, a decline in the level of beta-carotene and a quantitative loss in the Dl protein. Loss of the protein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…An enhanced content of free radicals and consequent lipid peroxidation during the stress treatment in MI may also be attributed to the stressinduced suppression of the scavenging potential of the chloroplasts. This notion is supported by a decreased level of β-carotene as reported previously in the clusterbean cotyledons under the same experimental conditions (Deo and Biswal 2001) and a decline in the activity of SOD observed in this study (Fig. 2).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…An enhanced content of free radicals and consequent lipid peroxidation during the stress treatment in MI may also be attributed to the stressinduced suppression of the scavenging potential of the chloroplasts. This notion is supported by a decreased level of β-carotene as reported previously in the clusterbean cotyledons under the same experimental conditions (Deo and Biswal 2001) and a decline in the activity of SOD observed in this study (Fig. 2).…”
Section: Discussionsupporting
confidence: 84%
“…Water stress was imposed by growing the seedlings in 3 % aqueous PEG-6000 solution under controlled conditions as described in Deo and Biswal (2001). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carotenoid plays an important role in photoprotection of chlorophyll (Deo and Biswal, 2001) by quenching the triplet Chlorophyll and scavenging the singlet oxygen and other reactive oxygen species (ROS) (Choudhury and Behera, 2001). Edwin, 1997;Moreland, 1980;Bhuniaet al, 1991 suggested that the loss of carotenoid accumulation may be due to the inhibition of carotenoid biosynthesis pathway leading to chlorosis of the organism or may be due to degradation membrane component of the thylakoid (Allen, 1984).…”
Section: Results:-mentioning
confidence: 99%